Deposition of Cr films by hot target magnetron sputtering on biased substrates; Surface and Coatings Technology; Vol. 350 - Sidelev D. V. Dmitry Vladimirovich; Bestetti M. Massimiliano; Bleykher (Bleicher) G. A. Galina Alekseevna; Krivobokov V. P. Valery Pavlovich; Grudinin V. A. Vladislav Alekseevich; Franz S. Silvia; Vicenzo A. Antonello; Shanenkova Yu. L. Yuliya Leonidovna (2018, 2018)
Title screen